The Nicopior family in the mayoralty position in Libertad, Antique. - Domingo, Jenefer Patricio (2006.)
This is a descriptive study of the Nicopior family members who were elected as municipal mayors of Libertad. The study aims to identify the members of the Nicopior family who were elected as municipal mayors of Libertad, Antique and provide a political profile of each of them; to determine the factors that led the Nicopior family to enter and dominate Libertad?s politics; to find out the problems and difficulties faced by these politicians during their respective terms of office; to identify the programs and projects of each Mayor during their administrations; and to determine the role of the Nicopior family in the development of Libertad, Antique. The data were gathered from the municipal development plans, municipal profile, interviews with the Nicopior mayors and other key informants such as their close family members and relatives, political rivals, and political allies, souvenir programs, SUMPAY, the community newsletter of Libertad and library research (Antique Provincial Library, Center for West Visayan Studies library, and UPV Library). The researcher found out that there were three members of the Nicopior family that were elected as municipal mayors of Libertad, Antique. Factors such as support given by a prominent politician and strong political parties, supportive family and friends, and different sectors of the community, led the Nicopior family to enter and dominate Libertad?s politics. Financial problems, insurgency and the hard to please people of Libertad were some of the problems encountered by the Nicopior family during their terms of office. The programs and projects of the Nicopior mayors included infrastructure, agricultural enhancement, health, transportation, communication and education. Basically, majority of the developments in Libertad are because of the Nicopior mayors. Libertad became well-known to the rest of Antique and neighboring provinces for being the cleanest and greenest municipality of Antique, the mat- capital of Antique and boosting a zero- percent crime rate.
Research Paper (Undergraduated, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2006
Keywords: Nicopior Families -- Libertad, Antique -- Research